RETRIBUSI IZIN MENDIRIKAN BANGUNAN DAN PERMASALAHANNYA STUDI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA MANADO - Rorong, Richard Sem; Budiarso, Novi Swandari (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to determine the process of Building Permits (IMB) and the management of Regional Levies Determination Letters (SKRD) which are often not paid by the applicant, causing retribution receivables at the Manado City Investment and One Stop Integrated Service Office. This study uses an exploratory qualitative analysis method. Qualitative data obtained by interview, observation and study of documentation as well as the validity and reliability of the data is determined by triangulation of data for then the data obtained will be analyzed thematically and interpreted in order to draw conclusions. The results showed that the management of the IMB issuance experienced delays in the file processing process by the IMB technical team so that it had implications for the delay in the issuance of the IMB document. Another consequence that occurs is the loss of potential local revenue from IMB retribution due to delays. Receivable levies occur because the applicant does not pay the IMB SKRD at the bank